Digital Beam-Forming for Spaceborne Reflector- and Planar-Antenna SAR - A System Performance Comparison - Younis, Marwan; Huber, Sigurd; Patyuchenko, Anton; Bordoni, Federica; Krieger, Gerhard (IEEE Geoscience and Remote Sensing Symposium (IGARSS), 2009)
The trend in the conception of future spaceborne radar remote sensing is clearly towards the use of digital beam-forming techniques. These systems will comprise multiple digital channels, where the analog-to-digital converter is moved closer to the antenna. This dispenses the need for analog beam steering and by this the used of transmit/receive modules for phase and amplitude control. Digital beam-forming will enable Synthetic Aperture Radar (SAR) which overcomes the coverage and resolution limitations applicable to state-of-the-art systems. On the other hand, new antenna architectures, such as reflectors, already implemented in communication satellites, are being considered for SAR applications. The paper compares the system architecture and SAR performance of a planar and a reflector antenna SAR. ©2009 IEEE.
DLR Import::2019-04-03